Numerical model of three phase-three dimensional flow in porous media for reservoir simulation - Hai, Duong Ngoc; Ba, Dang The (Vietnam Journal of Mechanics, 2002)
The paper presents the results of simulation and study of mixture - oil, gas and water - flows in porous medium using three-phase, three dimensional "Black oil" model. For discretizing the system of mathematical equations, the finite volume difference method was used. To solve numerically the system of discretized equations the IMPES and iterative methods were chosen. The numerical results are compared with a number of analytical solution, experimental measurement and calculation results of the other authors and they shown a good agreement. The model can be developed, adapted and used for study and simulation of mixture - oil, gas and water - flow in different experimental and real field conditions.